DAYA HAMBAT EKTRAK ETANOL BUAH BELIMBING WULUH (Averrhoa bilimbi L) TERHADAP PERTUMBUHAN Staphylococcus aureus dan Staphylococcus epidermidis SECARA IN VITRO - Asri Rahmiati; Sri Darmawati; Ana Hidayati Mukaromah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Acne infection is caused inflammation of pilosebasea accompanied by accumulation of keratin material, caused by S. aureus and S. epidermidis bacteria. The community uses of wuluhstarfruit (Averrhoabilimbi L) as a traditional medicine to treat acne infection. Wuluh starfruit contains flavonoids, alkaloids, tannins, and saponins that act as anti microbial. The aim of this study was to analyze the inhibitory power of wuluh starfruit ethanol extract on the growth of S. aureus and S. epidermidis bacteria. The method used in this research is the diffusion of wells. This research used two types of bacteria. S.aureus and S.epidrmidis, each bacteria of the four treatment groups that is 10%w/v; 20%w/v; 30%w/v; 40%w/v; positive control of Ciprofloxacin, and negative control of sterile aquades. The research results of inhibitory power of ethanol extract of wuluh starfruit with variation of concentration 10 %w/v; 20 %w/v; 30 %w/v; and 40 %w/v successively in S.aureus was 21.6 mm; 27.0 mm; 31.3 mm; And 34.0 mm, whereas in S.epidermidis is 28.6 mm; 31.6 mm; 36.3 mm; And 39.0 mm. Then the positive control of Ciprofloxacin has an inhibit zone of 30.0 mm and 35.0 mm. While the negative control of sterile aquades is not formed inhibit zone. The result ofOne Way Anova statistic test on S. aureus is p=0.000 and S. epidermidis is p=0.000, because (p<0.05) hence result there is significant difference, so it can be concluded that the extract of wuluh starfruit ethanol can inhibit the growth of S. aureus and S. epidermidis and there is a significant difference between the variantconcentration ofethanol extract wuluhstarfruit. Keywords: Staphylococcus aureus, Staphylococcus epidermidis, Ethanol extract of wuluhstarfruit.